Rapid testing for improving uptake of HIV/AIDS services in people with HIV infection - Pottie, Kevin (Cochrane Database Syst Rev, 2018)
This is a protocol for a Cochrane Review (Intervention). The objectives are as follows: The aim of our review is to assess effects of rapid HIV testing strategies on HIV screening outcomes: (i) uptake; (ii) transport and costs, (iii) tradeoffs/possible harmful effects/false positives compared to traditional laboratory testing approaches. HIV screening outcomes also include completion of risk reduction counselling, and uptake of ARV treatment for people living with HIV, including pregnant women, and other HIV/AIDS treatments to reduce morbidity and mortality. The specific objectives of this review are to: 1) critically review and synthesize effectiveness evidence on rapid compared to conventional laboratory HIV testing approaches for community and facility‐based testing. 2) conduct sensitivity analysis to explore the effect modifiers (e.g. location of testing, population, link to treatment etc.) on HIV testing and treatment outcomes. The populations that are considered at high risk for HIV infection include people from HIV concentrated epidemic countries, ethnic minority groups, Aboriginal peoples, men who have sex with men (MSM), intravenous drug users, truckers, factory workers and sex workers (UNAIDS 2011).